Exploring the impact of “double carbon target” on environmental efficiency of coal cities in China - Zhang, Yuntong; Chen, Zhenling; Chen, Huihui; Mao, Junjie (Frontiers in Environmental Science, 2023)
Chinese government proposed the "Double Carbon Target" (DCT) in 2020 to deal with the increasing global warming crisis. In this regard, the study identifies temporal and spatial evolution characteristics of environmental efficiency through the DEA-SBM model and further explores the impact of DCT and the policy of solar energy on the environmental efficiency of coal cities. Empirical results show that: (1) Both economic efficiency and environmental efficiency of China's coal cities are first rising and then falling during the period 2003-2022, and the gap between coal cities and non-coal cities was very small before 2011, but it begins to be enlarged after 2011. The main reason is environmental regulation has exerted a significant impact on coal cities; (2) the difference in environmental efficiency among coal cities is huge due to their poliy for supporting solar energy. Some cities have broken carbon lock-in by the favourite policy for solar energy, while others have been trapped into path dependence on the coal-related industry; (3) generally, the more amount of emission reduction required, the lower the environmental efficiency of coal cities in the carbon neutralization scenario. Furthermore, some cities rich of solar energy resources, such as Erdos, and Xuzhou, still have better environmental performance under different carbon neutralization scenarios, while others will encounter many transformation barriers and even may cause a social crisis. Therefore,it is suggested that some coal cities in northwest China can vigorously develop solar energy to improve environmental efficiency.